Physiological and Subjective Responses Associated to Physical and Mental Load in a Simulated Task (2018)
Introduction: the objective is to develop a quasi-experimental study to know the changes in physiological responses and perceived efforts of a group of fifteen healthy students that performed a simulated task related with the operation of a CNC lathe in a lab environment. Materials and methods: The participants were asked to randomly complete a total of eight sessions including single and combined test of physical and mental load. Low/High Physical Load and Low/High Mental Load were established as independent variables. Heart rate, physical performance, mental performance, and effort perception were established as dependent variables. Conclusions: High load levels have a significant effect on the heart rate increasing, but not in the perception of effort. High levels of mental load have a significant effect on physical and mental performance.